Evaluation of the Magnet Breakaway Force Measurement Accuracy of the NT-800 Sensors for Early Detection of Defects of Their Manufacturing - A. Yu. Kutsepau; A. P. Kren; Y. V. Hnutsenka (Приборы и методы измерений)
Сontrol of mechanical stresses formed with the deposition of nickel coatings plays an important role in the diagnosis of coatings’ technical condition. Large internal stresses can lead to cracking or flaking of coatings which is completely unacceptable for critical parts and assembly units used, for example, in space technology for which reliability is of paramount importance. An important aspect of internal stresses monitoring is the measurement error of the instruments used. The purpose of this work was to determine the characteristics of the device sensors, which make the assessment of their manufacturing possible at the preliminary stage of the measuring equipment assembling in order to maintain the required accuracy of subsequent measurements.In most cases the measurement error assessment is possible only after the equipment manufacture and calibration. In this paper it is proposed to evaluate the accuracy characteristics of device sensors based on the precision (repeatability and reproducibility) of the primary informative parameter recording. In the case of the NT-800 device that was developed at the Institute of Applied Physics of the National Academy of Sciences of Belarus the effect of precision characteristics deterioration on the eventual measurement error is demonstrated. Determining the precision parameters before establishing correlation dependences between the primary informative parameter and the measured characteristic is proposed in order to reject poorly manufactured sensors and reduce labor costs.In particular, measurements of the magnitude proportional to the magnetic breakaway force were carried out using the NT-800 device with nickel specimens simulating coatings with a thickness of 200 to 700 μm and a rolling value from 0 to 40 %. It was established that in the case of well-made sensors the variation coefficient calculated from the dispersion of repeatability is in the range 0.2–0.6 %, and the variation coefficient calculated from the dispersion of reproducibility does not exceed 0.9 %. In the case of a sensor with the sensitive element parameters worsened, the variation coefficient of repeatability and reproducibility were up by one and a half times. Deterioration of the precision characteristics resulted in significant changes in the readings of the calibrated instrument. Thus the absolute measurement error for a sensor with a poorly made sensitive element turned out to be approximately 3 times higher in the range of 200– 300 MPa than that for a sensor with good precision parameters.